Pure spin current polarizer enabled by antiferromagnetic insulator - Hetian Chen; Dingsong Jiang; Yujun Zhang; Xiaofu Qiu; Yuhan Liang; Qinghua Zhang; Fangyuan Zhu; Takuo Ohkochi; Mingfeng Chen; Yue Wang; Jingchun Liu; Qing He; et al. (Nature Communications)
Abstract Pure spin current enables the transport of spin information without charge flow, providing opportunities for next-generation information technologies. A pure spin current polarizer, capable of controlling both its transmittance and spin polarization, is critical for the development of spintronics; however, it has not yet been demonstrated. Here, we demonstrate a highly efficient pure spin current polarizer at room temperature using a single-domain antiferromagnetic insulator film, through structural engineering and spin-lattice coupling. Our device exhibits a large differential magnon current transmittance at room temperature. Remarkably, we find that the spin polarization of the transmitted magnon current aligns with the Néel vector of the polarizer. This enables a large modulation of damping-like torque and generation of out-of-plane-polarized magnon current, offering alternative routes for developing energy-efficient spintronic devices. We anticipate that this pure spin current polarizer will serve as a building block for spintronics based on pure spin current.